How to Improve Entrepreneurship Education in “Double High-Level Plan” Higher Vocational Colleges in China - Huang, Yangjie; Zhang, Yanzi; Long, Zehai; Xu, Da; Zhu, Ruijie (Frontiers in Psychology, 2021)
Entrepreneurship education complements vocational education in helping students develop their career prospects. This empirical study comprehensively analyzed sample data of 13,885 students from 40 “Double High-level Plan” higher vocational colleges in China using robust standard error regression analysis and other methods. The results showed that Entrepreneurship Practice (EP), Entrepreneurship Curriculum (EC), and Integration of Entrepreneurship Education and Professional Education (IEEPE) have a significant positive effect on Entrepreneurship Education Performance (EEP), with EP being the most important factor. Furthermore, ascribed factors (gender, household registration, only child or not, whether parents have entrepreneurial experience) and self-achieved factors (double high-level type, school area, subject major, whether to accept social entrepreneurship education) were found to affect students’ perception of investment in entrepreneurship education. The study summarizes the existing problems of entrepreneurship education in “Double High-level Plan” higher vocational colleges and proposes four suggestions: pursue the integrated development of entrepreneurship education and “Double High-level” construction, advance both theoretical education and practical education, promote digital reform of the “three teaches” (teachers, teaching materials, and teaching methods), and develop entrepreneurship education in a comprehensive and balanced manner.